Hadis Tentang Pendidikan Anak Balita - Abdul Muiz (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2019)
This research article will examine the hadith about the education of toddlers. The method used is qualitative with the type of library research. Qualitative research is field research, namely research that aims to study intensively the background of the current situation and environmental interactions of a social unit, whether individual, group, institution or community. Field research is carried out by digging up data sourced from locations or research fields related to prices and promotions and their impact on sales volume in the company. While library research. Library research is research that is carried out using literature (library), either in the form of books, notes, or reports on the results of previous research. The results of this study are that early childhood education in the Islamic view is education that takes place from when the child is small or from knowing nothing to becoming knowledgeable. The purpose of early childhood education is to guard its growth period with good and correct education, so that children grow up to be pious children and are safe in the afterlife. The guidance and provision of educational materials in early childhood include: calling the call to prayer in the baby's ear, giving a good name, giving breast milk, aqiqah on the seventh day of birth, circumcision, and children's intellectual education.